Wind-sensitive urban planning and design: Precinct ventilation performance and its potential for local warming mitigation in an open midrise gridiron precinct. (May 2020) - He, Bao-Jie; Ding, Lan; Prasad, Deo
Abstract: Urban heat island (UHI) phenomenon is a severe issue faced by many cities and the reduction of urban ventilation is one of the significant causes. Reasonable urban planning and design can allow cooler wind penetration and thereby UHI mitigation. Upon the local climate zone, the precinct ventilation zone is developed at the local scale with the consideration of wind influence during planning and design. Nevertheless, the precinct ventilation performance (PVP) and its potential influence on precinct outdoor thermal environment (POTE) and precinct outdoor thermal comfort (POTC) have not been well understood. As a result, this study aims to examine PVP and its associated influence on POTE and POTC. This is achieved by a case study within an open midrise gridiron (OMG) precinct in Sydney, Australia during summertime. Result indicates the combinations of the OMG precinct with different external meteorological conditions (EMC) resulted in significant variations in PVP, POTE and POTC. Street orientation in the OMG precinct was not a determinant of PVP, POTE and POTC variations. Compared with the inland wind, sea breeze resulted in weaker UHII within the OMG precinct and more areas underwent cool island effects. Nevertheless, wind could not fully explain the variation of POTE and POTC, while it still had cooling potentials under specific conditions. When the sea breeze prevailed, wind exhibited its cooling potential under the combination of negative UHII and shading as well as that of positive UHII and solar exposure. Forced by the inland wind, precinct ventilation could still have cooling potential under positive UHII and solar exposure combination. Moreover, for cities like Sydney with not high air moisture, moisture increase could result in UHI mitigation and POTC improvement, which was also a way of sea breeze cooling under certain conditions. Afterwards, some implications for local warming mitigation through precinct planning and design have been presented. Overall, this study provides the understandings of the PVP and its associated influence on POTE and POTC within the OMG precinct, and can practically inform urban planners and designers with the wind-sensitive urban planning and design for local warming mitigation. Highlights: Co-impact of urban morphology and external meteorological condition on precinct ventilation. Different combinations of EMC and a specific precinct result in significant variations of PVP, POTE and POTC . Street orientation makes no difference to PVP, POTE and POTC within (gridiron) precincts. Precinct ventilation forced by sea breeze was better to UHII reduction, ΔRH improvement and ΔPET reduction. Wind exhibited its cooling potentials under certain conditions even under inland wind condition.